Smart Home Network Desıgn Usıng The Network Development Lıfe Cycle Method - Haeruddin Haeruddin; Tiara Tiara (CoMBInES - Conference on Management, Business, Innovation, Education and Social Sciences, 2021)
In this modern era, almost all electronic devices can be connected to a computer network. Not only electronic items such as smartphones, laptops, computers, household appliances can also be connected to a computer network. This is all thanks to the concept of a smart home which allows us to build any device in the home just by talking without supervision, and we can manage it through our closest device. Our life is easier because we do not need to exert much energy anymore. The purpose of this research is how to design and implement a network for a smart home using the Network Development Life Cycle method. This network design is connected to smart home devices such as routers, smart speakers, smart lamps, smart TVs, smartphones, and laptops. The interconnection media used are wired and wireless. The network to be implemented as a security system that is one of the accesses to IoT users and devices and has bandwidth settings so that all devices get bandwidth allocation so that they can be accessed easily